OPTIGOV - A new methodology for evaluating Clinical Governance implementation by health providers - Nardella Pierangela; Valerio Luca; Capizzi Silvio; Siliquini Roberta; La Torre Giuseppe; Specchia Maria; Campana Alessandro; Ricciardi Walter (BMC, 2010)
Abstract Background The aim of Clinical Governance (CG) is to the pursuit of quality in health care through the integration of all the activities impacting on the patient into a single strategy. OPTIGOV (Optimizing Health Care Governance) is a methodology for the assessment of the level of implementation of CG within healthcare organizations. The aim of this paper is to explain the process underlying the development of OPTIGOV, and describe its characteristics and steps. Methods OPTIGOV was developed in 2006 by the Institute of Hygiene of the Catholic University of the Sacred Heart and Eurogroup Consulting Alliance. The main steps of the process were: choice of areas for analysis and questionnaire development, based on a review of scientific literature; assignment of scores and weights to individual questions and areas; implementation of a software interfaceable with Microsoft Office. Results OPTIGOV consists of: a) a hospital audit with a structured approach; b) development of an improvement operational plan. A questionnaire divided into 13 areas of analysis is used. For each area there is a form with a variable number of questions and "closed" answers. A score is assigned to each answer, area of analysis, healthcare department and unit. The single scores can be gathered for the organization as a whole. The software application allows for collation of data, calculation of scores and development of benchmarks to allow comparisons between healthcare organizations. Implementation consists of three stages: the preparation phase includes a kick off meeting, selection of interviewees and development of a survey plan. The registration phase includes hospital audits, reviewing of hospital documentation, data collection and score processing. Lastly, results are processed, inserted into a final report, and discussed in a meeting with the Hospital Board and in a final workshop. Conclusions The OPTIGOV methodology for the evaluation of CG implementation was developed with an evidence-based approach. The ongoing adoption of OPTIGOV in several projects will put to the test its potential to realistically represent the organization status, pinpoint criticalities and transferable best practices, provide a plan for improvement, and contribute to triggering changes and pursuit of quality in health care.